Supramolecular Complexes of Plant Neurotoxin Veratridine with Cyclodextrins and Their Antidote-like Effect on Neuro-2a Cell Viability - Laura A. Uribe; Sandra Leonardo; Thorbjørn Terndrup Nielsen; Casper Steinmann; Mònica Campàs; Alex Fragoso (MDPI AG, 2022)
Veratridine (VTD) is a plant neurotoxin that acts by blocking the voltage-gated sodium channels (VGSC) of cell membranes. Symptoms of VTD intoxication include intense nausea, hypotension, arrhythmia, and loss of consciousness. The treatment for the intoxication is mainly focused on treating the symptoms, meaning there is no specific antidote against VTD. In this pursuit, we were interested in studying the molecular interactions of VTD with cyclodextrins (CDs). CDs are supramolecular macrocycles with the ability to form host-guest inclusion complexes (ICs) inside their hydrophobic cavity. Since VTD is a lipid-soluble alkaloid, we hypothesized that it could form stable inclusion complexes with different types of CDs, resulting in changes to its physicochemical properties. In this investigation, we studied the interaction of VTD with β-CD, γ-CD and sulfobutyl ether β-CD (SBCD) by isothermal titration calorimetry (ITC) and nuclear magnetic resonance (NMR) spectroscopy. Docking and molecular dynamics studies confirmed the most stable configuration for the inclusion complexes. Finally, with an interest in understanding the effects of the VTD/CD molecular interactions, we performed cell-based assays (CBAs) on Neuro-2a cells. Our findings reveal that the use of different amounts of CDs has an antidote-like concentration-dependent effect on the cells, significantly increasing cell viability and thus opening opportunities for novel research on applications of CDs and VTD.